Characterization of Pore Structure of Different Hardened Cement Pastes# - MARKJA, Irida; BIER, Thomas (International Journal of Computational and Experimental Science and Engineering, 2016)
The goal of this study is to characterize the hardened cement paste at 1, 7 and 28 days using a combination of Mercury Intrusion Porosimetry (MIP), X-Ray diffraction (XRD), Thermal Analysis (TA). Hardened mortars are porous materials their pore structure being developed during hydration as a function of water binder ratio, the binder’s chemical reactions and time. Different binder systems and as a consequence different chemical reactions will influence the pore structure. Systems such as Calcium Silicate Hydrate formation, Calcium Aluminate Hydrate formation are investigated with respect to the developing pore structure. MIP was used as a generally accepted technique for deriving porosity and pore size distribution and results correlated to those received from ESEM image analysis. MIP was used as a generally accepted technique for deriving porosity and pore size distribution and results correlated to those received from ESEM image analysis.